Mer de Norvége ou du Groënland, côte de Norvége - Vestfjorden, abords de Narvik - Ofotfjorden / d'après les cartes norvégiennes les plus récentes, Service hydrographique de la marine . 1940 - France. Service hydrographique de la marine; (1947)
Publication provisoire. Corr. . 1947 Relief shown by spot heights and hachures. Depths shown by bathymetric isolines and soundings.; Selected lights shown in orange.; Includes 1 inset map: Port de Narvik.; Pasteover at Ramsundet Color; 1:100,000